Analisis Reverberation Time terhadap Kenyamanan Audial pada Ruang Auditorium Menara Pinisi UNM - Zainatun Zainatun; Muhammad Ramli Rahim; Asniawaty Kusno (Jurnal Penelitian Enjiniring, 2018)
Auditorium space is one of the building functions that must be supported will be acoustic comfort. This research aimed (1) to determine the condition of auditory comfort in the auditorium space according to the opinion of the space users; (2) to investigate the value of the existing reverberation time in the space. The research used two methods, namely the qualitative and quantitative methods; the qualitative method was conducted by distributing questionnaires, interviews and direct observation in the field. The results of the questionnaires were analyzed using SPSS version 22, while the quantitative method was conducted by measuring the sound pressure level using the Sound Level Meter (SLM) and calculation of the Reverbertion Time (RT) by using the Sabine Equation and the simulation was conducted using the Ecotect Software. The research results indicated that, based on the questionnaires distribution to the space user, and according to the seat position, 44.3% of the older users felt comfortable about the spread of sound in the space, while 41.3% did not feel comfortable with the position of the seats and the sound they received, and only 2.0% felt very comfortable with the distribution spread of sound in the space. Meanwhile, the results of the measurement of the highest Level of Sound Pressure showed that at the measuring point of 31 was 94.0 dB and the lowest at point of 22 was 60.8 dB. The results of the RT calculation at the auditorium when the auditorium was empty was about 0.45-0.40 seconds at the frequency of 500hz.